A Binder‐Free and Free‐Standing Cobalt Sulfide@Carbon Nanotube Cathode Material for Aluminum‐Ion Batteries. Issue 2 (22nd November 2017) - Hu, Yuxiang; Ye, Delai; Luo, Bin; Hu, Han; Zhu, Xiaobo; Wang, Songcan; Li, Linlin; Peng, Shengjie; Wang, Lianzhou
Abstract: Rechargeable aluminum‐ion batteries (AIBs) are considered as a new generation of large‐scale energy‐storage devices due to their attractive features of abundant aluminum source, high specific capacity, and high energy density. However, AIBs suffer from a lack of suitable cathode materials with desirable capacity and long‐term stability, which severely restricts the practical application of AIBs. Herein, a binder‐free and self‐standing cobalt sulfide encapsulated in carbon nanotubes is reported as a novel cathode material for AIBs. The resultant new electrode material exhibits not only high discharge capacity (315 mA h g −1 at 100 mA g −1 ) and enhanced rate performance (154 mA h g −1 at 1 A g −1 ), but also extraordinary cycling stability (maintains 87 mA h g −1 after 6000 cycles at 1 A g −1 ). The free‐standing feature of the electrode also effectively suppresses the side reactions and material disintegrations in AIBs. The new findings reported here highlight the possibility for designing high‐performance cathode materials for scalable and flexible AIBs. Abstract : Binder‐free and free‐standing cobalt sulfide@carbon nanotubes are applied as the cathode for aluminum‐ion batteries with enhanced electrochemical performance. The optimized electrode exhibits a high capacity (315 mA h g −1 at 100 mA g −1 ), excellent rate performance, and remarkable cycling stability (297 mA h g −1 at 100 mA g −1 after 200 cycles; 87 mA h g −1 at 1 A g −1 after 6000 cycles).